2012
DOI: 10.1038/bjc.2012.71
|View full text |Cite
|
Sign up to set email alerts
|

Survival advantage observed with the use of metformin in patients with type II diabetes and colorectal cancer

Abstract: Background:Patients with type II diabetes mellitus (DM) have an increased risk of adenomatous colorectal (CRC) polyps and CRC cancer. The use of the anti-hyperglycemic agent metformin is associated with a reduced incidence of cancer-related deaths.Methods:We retrospectively evaluated the medical records of 4758 patients seen at a single institution and determined that 424 patients were identified by their physicians as having type II DM and CRC cancer. Data were subsequently acquired determining the subject's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
113
5
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(133 citation statements)
references
References 31 publications
8
113
5
4
Order By: Relevance
“…In a separate analysis of 212 postmenopausal women with colorectal cancer and type 2 diabetes, no statistically significant difference in colorectal cancer-specific survival was observed among users of metformin compared to non-users (HR 0.75, 95% CI 0.40-1.38) although unfortunately, the authors of this study were unable to obtain data on the timing of metformin use in relation to colorectal cancer diagnosis. 28 Other epidemiological studies investigating metformin use after colorectal cancer diagnosis and all-cause mortality and have indicated a beneficial effect with metformin use, 11,12 however these investigations are limited by small sample size and the use of only one exposure timepoint. Moreover, findings from studies which only examine the impact of metformin on all-cause mortality may be reflective of non-cancer mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In a separate analysis of 212 postmenopausal women with colorectal cancer and type 2 diabetes, no statistically significant difference in colorectal cancer-specific survival was observed among users of metformin compared to non-users (HR 0.75, 95% CI 0.40-1.38) although unfortunately, the authors of this study were unable to obtain data on the timing of metformin use in relation to colorectal cancer diagnosis. 28 Other epidemiological studies investigating metformin use after colorectal cancer diagnosis and all-cause mortality and have indicated a beneficial effect with metformin use, 11,12 however these investigations are limited by small sample size and the use of only one exposure timepoint. Moreover, findings from studies which only examine the impact of metformin on all-cause mortality may be reflective of non-cancer mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Although strong evidence supports the association of diabetes with crc, and recent work has examined metformin as a prognostic factor in crc, results are contradictory and tend to be related to specific patient populations [15][16][17][18][19] . In the present retrospective study, we set out to investigate whether metformin use in diabetic patients diagnosed with crc was associated with survival.…”
Section: Introductionmentioning
confidence: 99%
“…Metformin use has been associated with improved survival in patients with diabetes with breast [2], colorectal [3] and prostate cancer [4]; however there are limited data in lung cancer patients. Constitutive mTOR signaling plays an important role in the development of lung cancer and in vitro and animal studies have reported antiproliferative effects [5] and proapoptotic effects [6], as well as the inhibition of lung tumour growth [7].…”
Section: Introductionmentioning
confidence: 99%